(3CQLhRI aj GdJhMjOs - (3GdGhTj , Ydj Hf YKeGf Hf SdjeGf Hf eMeO GdJjej GdGhSj (B((3GdGhTj(B) (3GdaQZGfj GdMfaj, SQGL GdOjf CHh eMeO GdGhTj,J (B569 (3g` s ((3CMeO QaYJ s)
(3ChdgG (B:s
(3jbhd GdYHO ai HOA GdCeGdi dJhMjO HfXe cGddCdi s
(3BNQgG (B:s
(3hEf Gddg jLRi cd hbJ def HGdNjQ jhekG bO OYG di hUdi Gddg JYGdi Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B700s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1350s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds